Supporting shared decision making using an Option Grid for osteoarthritis of the knee in an interface musculoskeletal clinic: A stepped wedge trial. Issue 4 (April 2016) - Elwyn, Glyn; Pickles, Tim; Edwards, Adrian; Kinsey, Katharine; Brain, Kate; Newcombe, Robert G.; Firth, Jill; Marrin, Katy; Nye, Alan; Wood, Fiona
Highlights: The use of an Option Grid for osteoarthritis of the knee led to increased levels of shared decision making. Option Grid use led to increased levels of patient knowledge. Option Grid use led to increased levels of readiness to decide. Abstract: Objective: To evaluate whether introducing tools, specifically designed for use in clinical encounters, namely Option Grids, into a clinical practice setting leads to higher levels of shared decision making. Methods: A stepped wedge trial design where 6 physiotherapists at an interface clinic in Oldham, UK, were sequentially instructed in how to use an Option Grid for osteoarthritis of the knee. Patients with suspected or confirmed osteoarthritis of the knee were recruited, six per clinician prior to instruction, and six per clinician afterwards. We measured shared decision making, patient knowledge, and readiness to decide. Results: A total of 72 patients were recruited; 36 were allocated to the intervention group. There was an 8.4 point (95% CI 4.4 to 12.2) increase in the Observer OPTION score (range 0–100) in the intervention group. The mean gain in knowledge was 0.9 points (score range 0–5, 95% CI, 0.3 to 1.5). There was no increase in encounter duration. Conclusion: Shared decision making increased when clinicians used the knee osteoarthritis Option Grid. Practice Implications: Tools designed to support collaboration and deliberation about treatment options lead to increased levels of shared decision making.